Pengembangan API Berbasis JSON pada Sistem Koperasi Berbasis Web - Sutisnawati, Yayah; Mari Maryati; Angga Setiyadi (JEMBA, 2025)
This study aims to utilize JSON as a medium for data synchronization technology in a web-based cooperative system through the integration of API development and support for membership module management. The research consists of seven stages, namely: Problem Formulation, Literature Review, Data Requirement Analysis, Script Analysis of the Existing Membership System, JSON Implementation in the Membership Module, Data Synchronization Testing with Other Applications, and Conclusion. Based on the implementation and testing results, it can be concluded that to address the challenges in developing new systems for centralized web-based cooperative savings and loan systems, an integration architecture based on APIs was developed. By using a file named index_api.php as an intermediary, member information can be accessed by other applications without direct connection to the main database. The data exchange technology utilizes the JSON (JavaScript Object Notation) format due to its lightweight nature, readability, and compatibility across various platforms. This approach provides an effective solution as it enables the development of additional applications in a more flexible, secure, and structured manner without disrupting the existing core system. The integration through APIs and JSON technology opens up opportunities for broader, more efficient, and sustainable cooperative system development in the future